Proverbs as Vehicles of Truth in Contemporary English Fiction - Grzegorz Szpila (Armenian Folia Anglistika, 2007)
The article addresses one of the key issues of the studies of proverbs which refers to the use of proverbs in literature. The article is an attempt to reveal the attitude of the author and the character towards the proverbial truth. The traditional wisdom contained in a proverb can be either accepted or totally rejected. Besides these extremes, there is another situation when the characters of a literary text and/ or the author accept the proverbial truth to a certain extent. A proverb is applied in most diverse ways in literature starting from traditional interpretations to literary reinterpretations which serve the specific needs of the author.